2017
DOI: 10.1016/j.cej.2016.08.075
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the characteristic mixing time of solids and its link with the lateral dispersion coefficient in bubbling fluidized beds

Abstract: Experimental study on the characteristic mixing time of solids and its link with the lateral dispersion coefficient in bubbling fluidized beds, Chemical Engineering

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 50 publications
0
15
1
Order By: Relevance
“…The lateral dispersion coefficient is influenced by many operating conditions such as bed size, gas velocity, and particle property. However, researchers also found that the lateral dispersion coefficient may change significantly with the experimental techniques applied [25][26][27][28]. In addition, former research on lateral mixing of solids in fluidized beds mainly fit the lateral mixing process by the Fickian-type diffusion equation to derive the lateral dispersion coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…The lateral dispersion coefficient is influenced by many operating conditions such as bed size, gas velocity, and particle property. However, researchers also found that the lateral dispersion coefficient may change significantly with the experimental techniques applied [25][26][27][28]. In addition, former research on lateral mixing of solids in fluidized beds mainly fit the lateral mixing process by the Fickian-type diffusion equation to derive the lateral dispersion coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated mixing using this approach (e.g. 31,15,6,4,32,33 ), but most of these employ 2D simulations and, therefore, overestimate mixing rates because resistance to the hydrodynamics from the front and back walls is not accounted for. 3,4 Therefore, in order to understand and quantify mixing in commercial systems, this study employs fine-grid 3D simulations of a large pilot-scale 50 cm fluidized bed so that the hydrodynamics are independent of wall effects.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, when analysing the evolution of the Lacey mixing index (Equation 1), it can be extracted that the results obtained using the white area recognition method (Equation 2 al. [62]. Overall, it can be observed that the inclusion of the friction term in the simulations improves the prediction of the numerical results when compared with the experimental findings.…”
Section: Theorymentioning
confidence: 51%
“…The initial state has the theoretical maximum white area and the final state is reached when no white area is detected in the images. Further details of the processing of the experimental images can be found in Sánchez-Prieto et al [62].…”
Section: Experimental Data Processingmentioning
confidence: 99%
See 1 more Smart Citation